PARTISIPASI MASYARAKAT LOKAL DALAM PENGEMBANGAN OBJEK WISATA SEJARAH BATU KURSI PERSIDANGAN SIALLAGAN, DESA SIALLAGAN PINDARAYA, KECAMATAN SIMANINDO, KABUPATEN SAMOSIR - Deliana Sinaga; Arkilaus Wabia; Aidina Rizky Salsabilah (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
This research is motivated by the emergence of historical tours of the Siallagan court chair stone located in Siallagan Pindaraya Village. This study aims to see how the participation of local communities in the development of Siallagan tourism in Siallagan Pindaraya Village. The method used is observation and interviews with tourists and the surrounding community as well as using literature studies. From the results of the study concluded that the participation of local communities in this tourist attraction is very high. This is evidenced by the large number of community participation in developing tourist attractions by selling various souvenirs and providing supporting facilities for tourism activities such as: restaurants, accommodation (hotels/inns), and souvenir shops. And other participations, the community always applies Sapta Pesona Tourism in welcoming every tourist who comes to historical tourism objects in Siallagan Pindaraya Village.